2021
DOI: 10.1098/rsos.210239
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the cognitive abilities of a sex-changing fish species Labroides dimidiatus

Abstract: Males and females of the same species are known to differ at least in some cognitive domains, but such differences are not systematic across species. As a consequence, it remains unclear whether reported differences generally reflect adaptive adjustments to diverging selective pressures, or whether differences are mere side products of physiological differences necessary for reproduction. Here, we show that sex differences in cognition occur even in a sex-changing species, a protogynous hermaphroditic species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…We focussed on females because of their higher abundance and to strengthen the power of our analyses by avoiding to add another factor to the analyses. However, we know that cleaner fish males outperform females in the reversal learning task, while females outperform males in the detour task (Triki & Bshary, 2021). Therefore, we predict that adding males would not change the outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We focussed on females because of their higher abundance and to strengthen the power of our analyses by avoiding to add another factor to the analyses. However, we know that cleaner fish males outperform females in the reversal learning task, while females outperform males in the detour task (Triki & Bshary, 2021). Therefore, we predict that adding males would not change the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaners show various evidence for inhibitory control by detouring around barriers to reach a food source (Triki & Bshary, 2021), delaying gratification in order to receive a higher reward (Aellen et al, 2021) and being able to feed against preference (Bshary & Grutter, 2005). Also, cleaners perform very well in reversal learning tasks (Salwiczek et al, 2012; Triki & Bshary, 2021), which is the standard test for cognitive flexibility and where performance correlates with brain size in primates (Deaner et al, 2007). Working memory, the third important executive function, has not yet been tested in cleaners, but it has been shown that cleaners have very good long‐term memory (Triki & Bshary, 2019) and remember the ‘where’ and ‘when’ of interactions with clients (Salwiczek & Bshary, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a common Acanthurid species as client since they are one of the most frequent hosts for Labroides species in coral reefs [20]. We also selected female individuals to be consistent with past studies using L. dimidiatus as a model species and because gene functions may differ between sexes and can blur the analysis of molecular signals [26]. Fishes were habituated for 28 days to laboratory conditions.…”
Section: Materials and Methods (A) Experimental Setupmentioning
confidence: 99%
“…Cognitive scientists are becoming more and more aware that sexual selection has a role in driving differences between the sexes in cognitive traits and the behaviors associated with them. Across a wide-range of taxa, studies have found significant differences in females' and males' spatial cognitive abilities (Jones et al, 2003;Jonasson, 2005;Carazo et al, 2014;Lucon-Xiccato and Bisazza, 2017), reversal learning abilities (Lucon-Xiccato and Bisazza, 2014;Fuss and Witte, 2019;Triki and Bshary, 2021), problem-solving and innovation (Laland and Reader, 1999;Aplin et al, 2013), and ability to recognize a spatial-temporal pattern (Wallace et al, 2020). It is important to note that in many cases there is no sexual dimorphism in cognitive performance (Healy et al, 1999;Lucon-Xiccato and Bisazza, 2016), and the difficulty of ensuring equal motivation between the sexes in cognition tasks can be daunting (Rowe and Healy, 2014).…”
Section: Introductionmentioning
confidence: 99%